Karakteristik Uji Gramatur dan Daya Regang pada Kertas Berbahan Kulit Ubi dan Fiber Sawit - Titi Winda Sari; Ety Jumiati; Miftahul Husnah (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing demand for paper has led to a shortage of wood-based raw materials, thus requiring environmentally friendly alternatives. This study aims to analyze the physical, mechanical, and morphological characteristics of paper made from cassava peels (Manihot esculenta Crantz) and oil palm fruit fibers (Elaeis guineensis Jacq.) as eco-friendly paper raw materials. The research method involved pulp preparation through delignification using 3.5% HNO₃ and 3% NaOH, bleaching with 10% H₂O₂, paper sheet formation with varying compositions (A = 70:30, B = 50:50, C = 30:70, D = 10:90), followed by grammage testing and tensile strain testing. The results showed that the grammage values ranged between 96.3–99.7 g/m², while tensile strain ranged between 2.6–4.4%. The study concluded that the best composition was found in sample C (30% cassava peel : 70% palm fiber) with a grammage of 98.5 g/m² and tensile strain of 3.2%. The implication of this study is that cassava peel and palm fiber waste have the potential to serve as alternative paper raw materials that meet the quality standards of A-grade printing paper (SNI 7274:2008), while also supporting the reduction of dependence on wood.